2018
DOI: 10.1002/mus.26027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of peripheral neuropathy in nondiabetic children with chronic kidney disease

Abstract: Electrodiagnostic studies should be performed in children with CKD to assess for peripheral neuropathy for the purpose of optimizing medical care. Muscle Nerve 57: 792-798, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
(73 reference statements)
4
7
0
Order By: Relevance
“…In contrast, Ackil et al showed that sural nerve conduction abnormalities in 59% of children, and motor conduction studies revealed motor conduction abnormality in 29% of children on dialysis (19) . The tibial and common peroneal nerves were most commonly affected as there was reduced conduction velocity and amplitude in our patients, this in agreement with Yoganathan et al (26) . Another study reported that low peroneal nerve conduction velocity was considered as a sensitive measure for the diagnosis of uremic neuropathy (28) .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, Ackil et al showed that sural nerve conduction abnormalities in 59% of children, and motor conduction studies revealed motor conduction abnormality in 29% of children on dialysis (19) . The tibial and common peroneal nerves were most commonly affected as there was reduced conduction velocity and amplitude in our patients, this in agreement with Yoganathan et al (26) . Another study reported that low peroneal nerve conduction velocity was considered as a sensitive measure for the diagnosis of uremic neuropathy (28) .…”
Section: Discussionsupporting
confidence: 93%
“…Peripheral neuropathy prevalence in the current work was 22%; axonal motor and sensory neuropathy (81.8%) is more common than demyelinating motor neuropathy (18.2%). Yoganathan et al demonstrated that the prevalence of peripheral neuropathy was 52%; axonal neuropathy (80.8%) was more common than demyelinating neuropathy (11.5%) and motor neuropathy was the predominant type, followed by sensory motor neuropathy (26) . Few studies in children reported that the prevalence ranging from 0-59% (27) .…”
Section: Discussionmentioning
confidence: 99%
“…The current study illustrated normal motor and sensory nerve conduction of both the ulnar and median nerves on both sides in our polyneuropathy patients; this is in agreement with Yoganathan et al (28). Analytical interpretation of EMG results of the current study revealed normal motor units in 41 patients (82%), while nine patients (18%) revealed large polyphasic motor units (neuropathic).…”
Section: Discussionsupporting
confidence: 92%
“…Ackil et al (20) showed that 59% of children had sural nerve conduction abnormalities, and motor conduction abnormality was found in 29% of children on maintenance dialysis. The most common affected nerves were the tibial and common peroneal nerves as there was reduced conduction velocity and amplitude in our patients; this is in agreement with Yoganathan et al (28). Another study reported that low peroneal nerve conduction velocity was considered as a useful tool for uremic neuropathy detection (29).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation